PENINGKATAN KECERDASAN KINESTETIK MELALUI BERMAIN TARI KREASI DI TK B NURUL ILMI, BEKASI - Siti Kurniasih (Jurnal Evaluasi dan Pembelajaran, 2019)
The aims of this research were to describe the process of the increasing students’ kinesthetic intelligence and to knows how far the result of the increasing by students’ kinesthetic intelligence through creative dance playing. Respondent of the research involved of 14 children from grade B at Nurul Ilmi kindergarten. The method of this research was used by Kemmis and Taggart models and it does by 8 times of meeting by two cycles. The data analyzed by using quantitative and qualitative approach. The result of this research were an increasing by the students’ kinesthetic intelligence through creative dance playing, it was evidence by the quantitative and qualitative data. At the quantitative data it showed of precycle 50,09%, it was increase to cycle I 17,19% be 67,28%, and it was increase to cycle II 18,92% be 86,20%, then at the qualitative data shows the increasing of kinesthetic intelligence by process that the children is given a freedom for moving based on their imagination after analyzing the movement, miming the movement, classifying the movement, arranging in the movement, and showing the dance. Keywords: kinesthetic intelligence, creative dance playing, early childhood